The Moderating Effect of Location and Culture on the Relationship Between the Individual Determinants, External Factors and Firm Characteristics on Firm Performance - Lucky, Esuh Ossai-Igwe (2011)
The inconsistent result between the entrepreneurial factors and firm performance has made the researcher to propose a contingency model in which the effects of individual determinants, external factors and firm characteristics on firm performance are moderated by location and culture. The study focuses on the effect of location and culture on the relationship between entrepreneurial factors such as individual determinant, external factor and firm characteristics with firm performance. A cross-sectional study of questionnaire survey research design is conducted in this respect. Questionnaire data is generated from 182 entrepreneurs and owner-managers of small firms of both manufacturing and service industries where questionnaire are distributed through drop-off and pick procedure. The findings from the testing of the hypotheses indicate that there is a positive significant relationship between individual determinant, external factors and firm characteristics with firm performance. Location strongly moderates the relationship between external factor and firm characteristics with firm performance but location does not moderate the relationship between individual determinant and firm performance. Culture including cultural values, cultural beliefs and cultural practices do not moderate the relationship between individual determinant, external factor and firm characteristics with firm performance. On this note, the study recommends for the urgent need to be considered by the entrepreneurs, owner-managers and government to give serious considerations to the factor of location if they want to achieve the better firm’s performance and economy goals of the country. For the case of Nigeria, the issue of culture should be treated with caution. Finally, both the theoretical and practical implications are dully presented as well as that of the limitations of the study and suggestions for future study are included in this regard.